New-Onset Severe Cytopenia After CAR-T Cell Therapy: Analysis of 76 Patients With Relapsed or Refractory Acute Lymphoblastic Leukemia - Wang, Linqin; Hong, Ruimin; Zhou, Linghui; Ni, Fang; Zhang, Mingming; Zhao, Houli; Wu, Wenjun; Wang, Yiyun; Ding, Shuyi; Chang, Alex H.; Hu, Yongxian; Huang, He (Frontiers in Oncology, 2021)
Although chimeric antigen receptor T (CAR-T) cell therapy has proven to be effective in treating relapsed or refractory B-cell hematological malignancies, severe hematological toxicities remain an intractable issue. This retrospective study assessed the characteristics and risk factors of new-onset severe cytopenia following CAR-T cell infusion in 76 patients with r/r acute lymphoblastic leukemia. The rates of new-onset severe cytopenia were high, including severe neutropenia (SN) (39/56, 70%), severe anemia (SA) (35/66, 53%), and severe thrombocytopenia (ST) (31/64, 48%). Comparatively, cohorts with higher cytokine release syndrome (CRS) grades had higher incidence of severe cytopenia with prolonged duration. Multivariable analyses showed that elevated maximum (max) lg D-dimer and delayed peak time of CRS are independent risk factors for SN recovery; increased max lg IL-10 and delayed CRS recovery are risk factors for SA; high max lg ferritin is a risk factor for ST; and longer period to CRS onset or CRS recovery and higher grade of CRS are risk factors for prolonged hematological toxicities. These observations led to the conclusion that profiles of CRS, including its duration, severity and serum markers are correlated to the incidence and recovery of new-onset severe cytopenia, prompting clinical intervention for post-CAR-T severe cytopenia.